2021
DOI: 10.1093/infdis/jiab264
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Diabetes and Prediabetes on Mycobacterium tuberculosis Transmission to Close Contacts

Abstract: Background It is unknown whether dysglycemia is associated with M. tuberculosis transmission. Methods We assessed epidemiological and clinical characteristics of patients with culture-confirmed pulmonary TB and their close contacts, enrolled in a multicenter prospective cohort in Brazil. Contacts were investigated at baseline and 6 months after enrollment. QuantiFERON positivity at baseline and conversion (from negative to po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…In-vivo Mtb infections in diabetic mouse models display heightened lung inflammation and bacillary burden ( 50 , 51 ). This correlates with clinical observations of increased lesions, cavities and increased transmissibility of TB in T2D patients ( 52 , 53 ). Although the antigen-presenting ability of innate cells was not affected by hyperglycemia ( 54 ), altered cytokine production can affect the nature of the subsequent T-cell response contributing to poorer bacterial containment ( 48 ).…”
Section: Mycobacterium Tuberculosis and Metabolic Diseasesupporting
confidence: 89%
“…In-vivo Mtb infections in diabetic mouse models display heightened lung inflammation and bacillary burden ( 50 , 51 ). This correlates with clinical observations of increased lesions, cavities and increased transmissibility of TB in T2D patients ( 52 , 53 ). Although the antigen-presenting ability of innate cells was not affected by hyperglycemia ( 54 ), altered cytokine production can affect the nature of the subsequent T-cell response contributing to poorer bacterial containment ( 48 ).…”
Section: Mycobacterium Tuberculosis and Metabolic Diseasesupporting
confidence: 89%
“…Regional Prospective Observational Research for TB in Brazil (RePORT-Brazil) is a prospective observational cohort study of culture-confirmed pulmonary TB cases and their close contacts (Arriaga et al, 2021). There were five sites across three high TB-burden regions in Brazil: three in the southeast (Rio de Janeiro -Rio de Janeiro), one in the northeast (Salvador -Bahia), and one in the north (Manaus -Amazonas).…”
Section: Study Population and Follow-upmentioning
confidence: 99%
“…Brazil is a highly diverse upper-middle income country with large gaps in income equality and decreasing, yet still substantial TB burden. Our well-characterized multi-center cohort closely represents the TB patient population in Brazil and is well positioned to address this question (Arriaga et al, 2021). Based on preliminary data within our cohort (Souza et al, 2021;Arriaga et al, 2021), we hypothesized that female close contacts would have higher rates of IGRA positivity than men, even after adjusting for potentially confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“…Higher smear grades in patients with TB-T2D co-morbidity are indicative of higher lung mycobacterial burdens, suggesting that TB patients with T2D are more infectious than TB patients without co-morbidities [23]. A recent study from Brazil confirmed that TB patients with any form of dysglycemia (T2D or pre-diabetes) are more likely to transmit Mtb in a household contact setting [24].…”
Section: T2d Increases Tb Disease Severity and The Risk Of Adverse Tb Treatment Outcomesmentioning
confidence: 99%